Implementasi Program Mahasiswa KKN UMN Al-Washliyah dalam Menumbuhkan Kesadaran Anti Bullying di MIS Cendikia Kabupaten Batu Bara - Ismed Batubara; Venny Handayani; Miftahurrizki Miftahurrizki (Indo Publishing, 2025)
Bullying is a serious problem that persists frequently in elementary schools and negatively impacts students' psychological and social development, as well as their learning experience. Therefore, ongoing preventative efforts through early character education are necessary. This study aims to describe the role of Al-Washliyah Muslim Nusantara University (UMN) Community Service Program (KKN) students in fostering anti-bullying awareness within the MIS Cendikia school in Batu Bara Regency. A descriptive qualitative approach was used as data collection techniques, including direct observation, in-depth interviews, and activity documentation. The results indicate that the anti-bullying education program implemented by the KKN students, through interactive counseling, educational games, visual media, and an empathetic communication approach, increased students' understanding and awareness of the negative impacts of bullying. Furthermore, changes in student attitudes toward more respectful, cooperative, and empathetic behavior were observed. Support from the school also strengthened the program's effectiveness in creating a safer and more inclusive learning environment. Thus, the KKN students serve as agents of change in instilling anti-bullying values ​​and building a positive school culture.